Which One is More Preferable for Gen Z: TikTok or WhatsApp for Disaster Public Communication - Suko Widodo (Scriptura, 2026)
Indonesia is one of the world's most disaster-prone countries, making effective digital disaster communication essential, particularly for Generation Z, who rely heavily on social media as their primary source of information. This study aims to examine the preferences of Indonesian Generation Z in using TikTok and WhatsApp for disaster public communication and to identify the communication characteristics that make each platform effective. A qualitative approach was employed using six Focus Group Discussions involving 48 university students in Surabaya. Data were analyzed through thematic analysis to identify recurring patterns related to perceived urgency, message clarity, interactivity, and information shareability. The findings indicate that WhatsApp is perceived as the most effective platform for disseminating urgent disaster warnings due to its immediacy, trusted interpersonal networks, and rapid message delivery. In contrast, TikTok is preferred for providing explanatory, engaging, and memorable disaster information through visual storytelling and interactive features. Rather than favoring a single platform, participants consistently advocated a hybrid communication strategy that combines WhatsApp for initial emergency alerts and TikTok for subsequent educational and persuasive communication. This study contributes to disaster communication research by proposing a hybrid platform model that aligns with Generation Z's digital communication practices and offers practical implications for disaster management agencies in designing more effective digital public communication strategies.